The difficult transformation of a forced constitutional agreement into actual government policy. The Democratic Centre Union and its defunct Law on the Statute of Schools (LOECE) of 1980 - Sevilla Merino, Diego (Historia y Memoria de la Educación, 2016)
Under Franco’s Regime, private education, which was managed almost completely by the church, underwent considerable development in comparison to public education. With the arrival of democracy, the conservatives were willing to concede to some minimal changes, whereas the progressives had big reforms in mind. It is because of this that education was one of the most complicated topics to reach an agreement upon in the Constitution of 1978. In order to achieve a consensus, Article 27 was drafted in a way which allowed both conservatives and progressives to develop their educational policies in keeping with their ideology. The Law of Schools (LOECE) of 1980 was the first law regulating education in accordance with the Constitution. In passing this law, the Government of Adolfo Suarez, with the support of Manuel Fraga’s conservative party, Alianza Popular, and the regional nationalist right-wing parties, imposed its ideology favouring private education. When the groups from the left saw their proposals rejected they filed a complaint before the Constitutional Court, which in fact declared void some of the most important articles contained in the law. The basic consensus achieved during the drafting of the Constitution has not prevented important disagreements from arising afterwards. As a result, with every change of government there is also a change in the laws and in the way educational policies are developed.